(untitled) (Research, Society and Development, 2024)
The purpose of this study was to analyze in vitro the cyclic fatigue resistance of two different rotary systems, ProFile Vortex® (Dentsply Tulsa Dental, USA) and ProTaper® (Dentsply Maillefer, Switzerland), considering the number of cycles, time and size of the fractured portion of the instruments used in curved steel root canals in a device. Forty instruments were divided into two groups. Group A: twenty ProFile Vortex® instruments No. 25; 25mm; taper .06 and Group B: twenty ProTaper® F1 instruments; 25mm. After the instrument cleaning process, the cyclic fatigue resistance was evaluated by subjecting all instruments to dynamic testing in a device developed until the occurrence of visually detected fracture. The number of cycles until fracture, time expressed in seconds and the size of the fractured portion were recorded and descriptive statistics, Student’s t-test and the Mann-Whitney U test were performed. Profile Vortex® instruments showed higher cyclic fatigue resistance, time and size of the fractured portion of the instruments with statistical significance (P value <0.05) compared to Protaper® instruments. It was concluded that Profile Vortex® instruments completed a greater number of cycles and took longer to fracture compared to ProTaper® instruments. The fractured portion of the instrument in millimeters was greater for Profile Vortex® files.